Aggregation-induced emission from silole-based lumophores embedded in organic–inorganic hybrid hosts. Issue 39 (16th September 2021) - Lyu, Guanpeng; Southern, Thomas J. F.; Charles, Bethan L.; Roger, Maxime; Gerbier, Philippe; Clément, Sébastien; Evans, Rachel C.
Abstract : The incorporation of silole-based lumophores into a photoactive organic–inorganic ureasil host via covalent grafting or physical mixing results in enhanced photoluminescence through aggregation and host–guest energy transfer. Abstract : Aggregation-induced emitters – or AIEgens – are often symbolised by their photoluminescence enhancement as a result of aggregation in a poor solvent. However, for some applications, it is preferable for the AIE response to be induced in the solid-state. Here, the ability of an organic–inorganic hybrid polymer host to induce the AIE response from embedded silole-based lumophores has been explored. We have focussed on understanding how the incorporation method controls the extent of lumophore aggregation and thus the associated photophysical properties. To achieve this, two sample concentration series have been prepared, based on either the parent AIEgen 1, 1-dimethyl-2, 3, 4, 5-tetraphenylsilole (DMTPS) or the silylated analogue (DMTPS-Sil), which were physically doped or covalently grafted, respectively, to dU(600) – a member of the ureasil family of poly(oxyalkylene)/siloxane hybrids. Steady-state and time-resolved photoluminescence measurements, coupled with confocal microscopy studies, revealed that covalent grafting leads to improved dispersibility of the AIEgen, reduced scattering losses, increased photoluminescence quantum yields (up to ca. 40%) and improved chemical stability. Moreover, the ureasil also functions as a photoactive host that undergoes excitation energy transfer to the embedded DMTPS-Sil with an efficiency of almost 70%. This study highlights the potential for designing complex photoluminescent hybrid polymers exhibiting an ehanced AIE response for solid-state optical applications.